Structure and cohesive energy of dipolar helices. Issue 12 (18th February 2016) - Stanković, Igor; Dašić, Miljan; Messina, René
Abstract : A striking non-monotonic behavior is reported for the cohesive energy and ground state polarization order parameter as a function of the surface packing fraction. Comparative microstructures (A–F) are depicted on the right panel. Abstract : This paper deals with the investigation of cohesive energy in dipolar helices made up of hard spheres. Such tubular helical structures are ubiquitous objects in biological systems. We observe a complex dependence of cohesive energy on surface packing fraction and dipole moment distribution. As far as single helices are concerned, the lowest cohesive energy is achieved at the highest surface packing fraction. Besides, a striking non-monotonic behavior is reported for the cohesive energy as a function of the surface packing fraction. For multiple helices, we discover a new phase, exhibiting markedly higher cohesive energy. This phase is referred to as ZZ tube consisting of stacked crown rings (reminiscent of a pile of zig-zag rings), resulting in a local triangular arrangement with densely packed filaments parallel to the tube axis.